Barriers and opportunities to measuring oncology patient navigation impact: Results from the National Navigation Roundtable survey. (14th June 2022) - Battaglia, Tracy A.; Fleisher, Linda; Dwyer, Andrea J.; Wiatrek, Dawn E.; Wells, Kristen J.; Wightman, Patrick; Strusowski, Tricia; Calhoun, Elizabeth; ,
Abstract : Background: Patient navigation improves cancer care delivery for those most at risk for poor outcomes. Lack of sustainable funding threatens the full integration of navigation services into health care delivery systems. Standardized navigation metrics that document impact and identify best practices are necessary to support sustainability. Methods: The National Navigation Roundtable administered a web‐based, cross‐sectional survey to oncology patient navigation programs to identify barriers and facilitators to the use of navigation metrics. The 38‐item survey asked about data‐collection practices and specific navigation metrics used by the program. Exploratory and descriptive statistics were used to identify factors associated with data collection and reporting. Results: Seven hundred fifty respondents from across the country represented navigation programs across the continuum of care. Although 538 respondents (72%) reported participating in routine data collection, only one‐half of them used data for reporting purposes. For the 374 programs that used electronic health records, only 40% had discrete, reportable navigation fields, and 25% had an identifier for navigated patients. Program funding was identified as the only characteristic associated with data collection, whereas the type of data collected was associated with work setting, participation in alternative payment models, and where on the continuum navigation services are provided. Respondents participating in an oncology accreditation program were more likely to collect specific outcome metrics across the continuum and to use those data for reporting purposes. The most common barriers to data collection were time (55%) and lack of support for complex data systems and/or platforms (50%). Conclusions: Inconsistent data collection and reporting of oncology navigation programs remain a threat to sustainability. Aligning data collection with oncology accreditation, funding, and reimbursement is a viable path forward. Abstract : Inconsistent data collection and reporting of oncology navigation programs remain a threat to sustainability. Aligning data collection with oncology accreditation and reimbursement is a viable path forward to the financial viability of navigation programs in cancer care.